2002
DOI: 10.1007/s002201000569
|View full text |Cite
|
Sign up to set email alerts
|

Nonassociative Star Product Deformations for D -Brane World-Volumes in Curved Backgrounds

Abstract: We investigate the deformation of D-brane world-volumes in curved backgrounds. We calculate the leading corrections to the boundary conformal field theory involving the background fields, and in particular we study the correlation functions of the resulting system. This allows us to obtain the world-volume deformation, identifying the open string metric and the noncommutative deformation parameter. The picture that unfolds is the following: when the gauge invariant combination ω = B + F is constant one obtains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
280
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(287 citation statements)
references
References 65 publications
7
280
0
Order By: Relevance
“…In [19] the deformation of D-brane world-volumes in the presence of NS-NS curved backgrounds was investigated in a nonsupersymmetric context. It was shown that, if both the brane and the background are curved, i.e.…”
Section: Discussing Associativitymentioning
confidence: 99%
See 1 more Smart Citation
“…In [19] the deformation of D-brane world-volumes in the presence of NS-NS curved backgrounds was investigated in a nonsupersymmetric context. It was shown that, if both the brane and the background are curved, i.e.…”
Section: Discussing Associativitymentioning
confidence: 99%
“…H ≡ d(B + F ) = 0, then the deformation of the world-volume is a Kontsevich deformation which defines a nonassociative, noncommutative product. Noncommutativity is governed by the usual NS-NS B-field, whereas nonassociativity arises from the NS-NS field strength H. This suggests that our supergeometries might naturally appear, if an analysis similar to [19] were to be performed in a manifestly supersymmetric formalism (i.e. working with a Green-Schwarz [20] or Berkovits [21] string) for backgrounds with nonvanishing super p-form field strengths.…”
Section: Discussing Associativitymentioning
confidence: 99%
“…Taking into account the algebra (3.5) and the commutation relation among the operators U i , we obtain 70) namely the present situation is already associative. This is expected, since the f flux does not arise from a p-form source, but it is a metric flux.…”
Section: Resolution Of Non-associativity and Flux Quantizationmentioning
confidence: 95%
“…Let us note that such a term was also obtained in Refs. [70,71] from the expansion of the Dirac-Born-Infeld action. The second and the third H-dependent terms appear as (parts of) the Chern-Simons action.…”
Section: Gauge Theory With Fluxesmentioning
confidence: 99%
“…To each of these theories, there corresponds, more generally, a twisted version. Twisted Poisson manifolds were first considered in some quantization problems in string theory [22,105], then they were defined as geometric objects [62,113], and finally viewed as particular cases of Lie algebroids with twisted Poisson structures [111,72]. Just as a Lie algebra with a triangular r-matrix gives rise to a Lie bialgebra in the sense of Drinfeld [29], a Lie algebroid with a Poisson structure gives rise to a Lie bialgebroid in the sense of Mackenzie and Xu [95,64], while a twisted Poisson structure gives rise to a quasi-Lie-bialgebroid 2 .…”
Section: Introductionmentioning
confidence: 99%